Halal Lifestyle Training for MA Rohmaniyyah’s Students: The Islamic Lifestyle Practice of Today’s Adolescent - Hermawan Adinugraha, Hendri; Rahmawati, Ferida; Sartika, Mila; Isthika, Wikan; Wikan Kinasih, Hayu (Amala Jurnal Pengabdian Kepada Masyarakat, 2022)
Based on the analysis of the situation, it is known that currently the concept of halal is universal for both Muslims and non-Muslims, halal does not only cover the needs of sharia, but is also a concept of sustainability through aspects of an Islamic lifestyle. The purpose of implementing this service is to add insight/knowledge of partners in the field of Halal lifestyle (HLS), to help partners to be able to practice Halal lifestyle (HLS) as an Islamic lifestyle for today’s youth, to provide convenience for MA Rohmaniyyah students in choosing a style. Islamic life through Halal lifestyle (HLS). The method of implementing this activity uses an educational approach, counseling (socialization) and Halal lifestyle (HLS) training for teenagers. Then, in addition to a model or method of Halal lifestyle (HLS) that has been generated. This service concludes that the majority (92%) of the students of MA Rohmaniyyah Mranggen understand that the word halal means allowed and the rest said halal means good. They interpret the halal lifestyle as having good morals or attitudes according to sharia or polite behavior. Examples of the halal lifestyle they have ever done are religious tourism, saving in Islamic financial institutions, wearing the syar’i hijab. The reason they consider it important to live a halal lifestyle is because the halal concept is universally applicable as rahmatan lil ‘alamin, or because a halal lifestyle can make the body healthy, or because a halal lifestyle can increase dignity. The way to live a halal lifestyle is by practicing the 3 HM concept, namely it is halal to obtain it, halal to consume it, and halal to use it. All of the students of MA Rohmaniyyah Mranggen intend/interested in a halal lifestyle.